Murabahah Funding Structure As Alternative Instrument For Islamic Financial Application - Kamaruddin Arsyad; Muhammad Rum; Sudirman Sudirman (Prodi Ekonomi Syariah IAIN Sorong, 2021)
Financing is an activity that is very important because with financing will be obtained the main source of income and become a supporting business continuity of the bank. Conversely, if the management is not good it will cause problems and the bank's business will cease. Therefore it is necessary to have a good Islamic financing management so that distribution and / or in this case financing to customers can be effective and efficient in accordance with the objectives of the company and the Islamic law itself. This paper tries to explain how the concept of Islamic finance management in the Murabahah application review itself so that it is expected that both the writer and the community can better understand the policies in Islamic finance management. The policy in Murabahah funding is very important from buying and selling and the principle of the contract, because this is done by the financing agent itself and is not related to buying and selling murabahah itself. Thus the policy standard in murabahah needs to be a cautious attitude, in determining, controlling, and collecting